2013
DOI: 10.1021/sc300164y
|View full text |Cite
|
Sign up to set email alerts
|

Thioether-Functionalized Vegetable Oils: Metal-Absorbing Biobased Ligands

Abstract: Vegetable oils containing thioether groups have been synthesized and used to effectively remove heavy metal ions from aqueous solution. The use of thioether-functionalized corn oil (TF-corn oil) and thioether-functionalized canola oil (TF-canola oil) were both effective in the extraction of Ag+ from a 600 ppm aqueous silver nitrate solution. The TF-corn oil reduced the observed silver in solution to a level below the detection limit, whereas the TF-canola oil was only able to remove slightly over 50% of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 21 publications
(29 reference statements)
5
25
1
Order By: Relevance
“…Equilibrium data for the separation of Ag + ions from an aqueous solution by adding thioether‐functionalized vegetable oils were reported earlier (Murray et al, ). These results were obtained by mixing oil and aqueous phases continuously by a magnetic stir bar for 11 days.…”
Section: Adsorption Isotherms and Kineticsmentioning
confidence: 65%
See 4 more Smart Citations
“…Equilibrium data for the separation of Ag + ions from an aqueous solution by adding thioether‐functionalized vegetable oils were reported earlier (Murray et al, ). These results were obtained by mixing oil and aqueous phases continuously by a magnetic stir bar for 11 days.…”
Section: Adsorption Isotherms and Kineticsmentioning
confidence: 65%
“…The second 4.00 mL solution was mixed with 0.2013 g TFCO to run the separation experiment. Experience from the earlier study (Murray et al, ) showed that agitation of the oil‐aqueous mixture sometimes caused the formation of an emulsion that made the ongoing analysis of the M n + concentration in the aqueous phase problematic. Therefore, the mixed contents in the present experiments were agitated for 60 s at 3200 rpm using a Vortex Genie 2 mixer from Fisher Scientific (Waltham, MA, USA).…”
Section: Separation Experimentsmentioning
confidence: 99%
See 3 more Smart Citations